“Pillole” destinate all’etere: le Proesie di Sardelli, Filidei e Crousaud - Scalfaro, Anna (Mimesis Journal, 2023)
The essay focuses on a cycle of very short pieces (one to two minutes) by Francesco Filidei for soprano solo on texts from Federico Maria Sardelli’s collection Proesie. During the lockdown, the composer created one musical Proesia per day; the singer Jeanne Crousaud performed them on video, taking care of a particular staging for each one, and posted them on Facebook. Through Sardelli’s ironic, surreal and often irreverent lyrics, Filidei intended to express through music the (emotionally varia- ble) psychological impact of quarantine. Starting by highlighting some of the salient features of the composer’s musical writing - the sophisticated formal construction of these (only apparently disengaged) pieces, in which moment after moment the slight alterations of pitches and rhythmic values take on a gestural value - the essay will dwell on the particular qualities of the staging, curated by Crousaud in agreement with Filidei. Each video, in fact, involves an appropriate realisation, connected to the meaning of the literary text and the gestural implications of the music. Finally, it will be highlighted how the characteristics of extreme brevity and the playful-ironic aspects of these performances are particularly suited to the audiovisual medium of the social network.